2016
DOI: 10.1152/physiolgenomics.00046.2015
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation patterns of homeobox genes in proximal and distal colon epithelial cells

Abstract: Region and cell-type specific differences in the molecular make up of colon epithelial cells have been reported. Those differences may underlie the region-specific characteristics of common colon epithelial diseases such as colorectal cancer and inflammatory bowel disease. DNA methylation is a cell-type specific epigenetic mark, essential for transcriptional regulation, silencing of repetitive DNA and genomic imprinting. Little is known about any region-specific variations in methylation patterns in human colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 67 publications
4
9
0
Order By: Relevance
“…S2A). Consistent with previous reports [31][32][33][34] a higher proportion of non-methylated CCGG sites (DNA methylation score 30) fell within the vicinity of the transcription start sites (TSS) of genes ( §2 kb). The distribution in this region was bimodal, whereas other genomic locations such as the gene body and intergenic regions were predominantly methylated ( Fig.…”
Section: Genome Wide Patterns Of Dna Methylationsupporting
confidence: 91%
See 3 more Smart Citations
“…S2A). Consistent with previous reports [31][32][33][34] a higher proportion of non-methylated CCGG sites (DNA methylation score 30) fell within the vicinity of the transcription start sites (TSS) of genes ( §2 kb). The distribution in this region was bimodal, whereas other genomic locations such as the gene body and intergenic regions were predominantly methylated ( Fig.…”
Section: Genome Wide Patterns Of Dna Methylationsupporting
confidence: 91%
“…Results illustrated the relationship between CCGG rich and depleted regions and the relative DNA methylation state at these regions. As reported previously, 34 the proportion of CCGG sites was higher at the TSS, becoming relatively depleted up and downstream of the TSS. However, DNA methylation decreased in close proximity to TSS (mean score D 21.0 at the TSS) and then increased both up-and down-stream from each TSS peak (mean score D 74.1 §2 kb from TSS) ( Fig.…”
Section: Genome Wide Patterns Of Dna Methylationsupporting
confidence: 86%
See 2 more Smart Citations
“…The Cancer Genome Anatomy Project (CGAP) functional grouping of the differentially expressed genes revealed major pathways implicated in colon cancer including epidermal growth factor (EGF), transforming growth factor beta (TGF-β), Wnt, Ras, insulin, and integrin signaling [77]. Differences in gene expression between the proximal and distal colon may result from the observed differential DNA methylation patterns in colonocytes [78]. Studies comparing cancers of the proximal and distal colon have revealed numerous differences in molecular and clinicopathological features, which reflect different susceptibilities to neoplastic transformation, such as the frequency of V-Ki-Ras2 Kirsten Rat Sarcoma 2 Viral Oncogene Homolog (KRAS) and B-Raf Proto-Oncogene, Serine/Threonine Kinase (BRAF) mutations, and the prevalence of MSI [7981].…”
Section: Host and Microbe-associated Alterations As Contributors Tmentioning
confidence: 99%